Performance analysis of MANET using elliptic curve cryptosystem - Kumar, A.; Aggarwal, A.; Charu, C. (2012 14th International Conference on Advanced Communication Technology (ICACT), 2012)
In this work various elliptic curve are compared and evaluated based on their operations i.e. Addition and Doubling. Out of these elliptic curves classical weierstrass and jacobian elliptic curves are selected to implement in MANETs (Mobile Ad Hoc Networks) and further network performance is analyzed to calculate efficient processing unit in a partially distributed key management environment. To manipulate the efficient processing unit various fast processing algorithms are selected and compared. Performance of these algorithms are evaluated in MANET using AODV (Ad-Hoc On Demand Distance Vector), DSDV(Destination Sequenced Distance Vector) and DSR(Dynamic Source Routing) protocols for small to medium scale networks. Results are compared to find the best routing and computational algorithm.